2015
DOI: 10.2147/ijn.s74514
|View full text |Cite
|
Sign up to set email alerts
|

Toward a magic or imaginary bullet? Ligands for drug targeting to cancer cells: principles, hopes, and challenges

Abstract: There are many problems directly correlated with the systemic administration of drugs and how they reach their target site. Targeting promises to be a hopeful strategy as an improved means of drug delivery, with reduced toxicity and minimal adverse side effects. Targeting exploits the high affinity of cell-surface-targeted ligands, either directly or as carriers for a drug, for specific retention and uptake by the targeted diseased cells. One of the most important parameters which should be taken into consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 176 publications
0
25
0
Order By: Relevance
“…Despite promising effects, AF is also associated with dose-limiting pulmonary toxicity. This and other drugs that display negative off-target effects can be re-evaluated using NP-based delivery systems that can deliver drug more specifically to targeted tumor tissues due to their passive (i.e., via the EPR effect) and active (i.e., receptor-mediated) tumor-targeting abilities [45, 46]. Drug nanocarriers can potentially increase the therapeutic index of the drug while reducing undesirable off-target effects and systemic toxicity [47].…”
Section: Discussionmentioning
confidence: 99%
“…Despite promising effects, AF is also associated with dose-limiting pulmonary toxicity. This and other drugs that display negative off-target effects can be re-evaluated using NP-based delivery systems that can deliver drug more specifically to targeted tumor tissues due to their passive (i.e., via the EPR effect) and active (i.e., receptor-mediated) tumor-targeting abilities [45, 46]. Drug nanocarriers can potentially increase the therapeutic index of the drug while reducing undesirable off-target effects and systemic toxicity [47].…”
Section: Discussionmentioning
confidence: 99%
“…These include monoclonal antibodies, single-chain variable fragments (scFvs), antigen-binding fragments (Fabs), single domain antibodies (sdAb), DARPins, peptides, aptamers, and small molecules (Fig. 9) [282284]. Monoclonal antibodies consist of two immunoglobulin (Ig) heavy chains and two Ig light chains, each with constant and variable domain regions.…”
Section: Approaches To Alleviate the Np-associated Adverse Effectsmentioning
confidence: 99%
“…Fabs consist of a single constant and variable domain form each heavy and light chains. Compared to conventional IgG antibodies (~150kDa), single-chain variable fragment (scFv) antibodies (~27kDa) and antigen-binding (Fab) fragments (~57kDa) are smaller in molecular size and weight [282,285,286]. …”
Section: Approaches To Alleviate the Np-associated Adverse Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional reviews on the EPR effect and nanomedicine can be found elsewhere. 39, 43 Once accumulated in tumors by the EPR effect, active targeting can be achieved by decorating outer surface of nanoparticles with targeting agents (homing targets), 44 such as monoclonal antibodies, single-chain variable fragments (scFv), targeting peptides, transferrin, folic acid, and aptamers. This strategy exploits the binding between targeting agents and receptors (or other membrane proteins) on the tumors, which is followed by cellular uptake of the particles termed receptor-mediated endocytosis.…”
Section: Nanoparticles For Sirna Delivery: Common Rationale and Comentioning
confidence: 99%